Impact of roof design on energy consumption and thermal comfort in urban residential buildings - Muhammad Taimur Sarwar; Mohsan Hassan; Sajjad Fahim; Edrisa Jawo (AIP Advances)
Energy demand is increasing rapidly to provide thermal comfort in buildings, globally. The rate of urbanization is also growing on a massive scale. Human thermal comfort is one of the primary needs in residential buildings in the current scenario. Air conditioning is contributing to energy consumption at a massive scale in the residential and commercial sectors. The roof of any building acts as the most crucial component as it absorbs maximum solar and heat gain during hot weather. The elements of the building envelope should be designed to minimize human discomfort. This paper investigates the thermal gain of different types of roofs in residential buildings in Lahore city and compares their performance to study their impacts on the indoor environments of the buildings. Five distinctive kinds of roofs have been selected for this research: flat roof, pyramid roof, hipped roof, gable roof, and shed roof. Computational results of solar analysis, building performance, and heating and cooling loads of the building are obtained for these roofs and compared to identify the most energy-efficient roof. These results are computed through the Revit 2025 software. The results show that flat roof design is the most energy-efficient, while shed roofs, especially sun-oriented ones, are the most energy-intensive due to their geometry. The results of this investigation are useful for engineers, researchers, dwellers, and architects to better understand the benefits of roofs according to their form to reduce energy demand in dwellings and make them sustainable and energy-efficient.